Pembekalan Keterampilan Wirausaha dan Implementasi Penjualan Bagi Anak Panti Asuhan Nurul Iman - Alqhani, Adip; Juniwati, Juniwati; Meliani, Dwi Rosita; Videlya, Viola; Amalia, Joezka; Karlina, Tety (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Children in orphanages often face challenges in the form of low self-efficacy, lack of exploration of potential, and a mindset that fulfilling basic needs is enough to survive, this condition inhibits their readiness towards social and economic independence. This service programme was carried out at Panti Asuhan Nurul Iman, Pontianak, with the aim of equipping foster children through experiential learning. The series of activities included entrepreneurship education, visits and mentoring by MSME partner Kopi Bubuk Bang Azis, market surveys in the Car Free Day (CFD) area, and practice selling products made by participants. Evaluation was conducted through observation, debriefing, and pre-post intervention questionnaires. The results showed a significant increase from 4 children who understood the basic concepts of entrepreneurship to 19 children after the programme. The success of selling out all products is a concrete validation of the effectiveness of experiential learning methods. Overall, this programme succeeded in increasing the understanding of entrepreneurship, building self-confidence, and instilling a foundation of socio-economic independence for the foster children of Nurul Iman Orphanage.